2013
DOI: 10.1186/1749-8090-8-163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of venovenous extracorporeal membrane oxygenation on the heart in a healthy piglet model

Abstract: BackgroundCardiac function is important for patients treated by venovenous extracorporeal membrane oxygenation (VV ECMO), but data about the effect of VV ECMO on the heart in nonneonates is absent. We studied the effect of VV ECMO on cardiac performance, cardiomyocyte and mitochondria in an animal model.MethodsTwelve farm piglets were randomly assigned into two groups: control group and ECMO group. In the ECMO group, ECMO cannulaes were placed and ECMO was instituted. Hemodynamics was recorded at baseline, 1 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…Our previous research suggested that immune mediated inflammation occurs 2 h after initiating ECMO therapy. After 24 h of ECMO therapy, multiple organs, such as the kidney, brain, and myocardium, upregulated expression of inflammatory cytokine [ 12 - 14 ]. In addition, a few rare clinical case reports suggest that ECMO therapy may increase serum endotoxin [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous research suggested that immune mediated inflammation occurs 2 h after initiating ECMO therapy. After 24 h of ECMO therapy, multiple organs, such as the kidney, brain, and myocardium, upregulated expression of inflammatory cytokine [ 12 - 14 ]. In addition, a few rare clinical case reports suggest that ECMO therapy may increase serum endotoxin [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…ECMO is a relatively new technology; therefore, further research is needed to ascertain its clinical utility. Our previous studies revealed that ECMO therapy may injure the heart [ 12 , 13 ], kidney [ 14 ], and brain [ 15 ]. Other recent case reports show that ECMO therapy can increase intra-abdominal pressure [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Levels of pro-in ammatory cytokines rise rapidly [20][21][22], which, in association with activation of the complement and contact systems, results in leukocyte activation [23]. This innate immune response, if severe, persistent or unchecked by a compensatory anti-in ammatory response (CARS), may lead to endothelial injury, disrupted microcirculation, and end organ dysfunction [24,25]. Under the condition of good perfusion of main organs and tissues, according to the histopathological evaluation of our experiment, we found that the in ammatory reaction caused by ECMO circuit itself may be at a low level, it had little effect on the function of main organs and tissues in sheep.…”
Section: Discussionmentioning
confidence: 99%
“…22 Indeed, in another preclinical model, the use of V-V ECMO was associated with mild myocardium injury, which had no effect on cardiac performance. 23 Further studies are needed to clarify the effects of extracorporeal circulation on RV function and its clinical implications.…”
Section: Discussionmentioning
confidence: 99%